The Butterfly Effect in Kim Stanly Robinson’s Aurora (International Journal of Food and Nutritional Sciences, 2022)
Aurora is a novel by Kim Stanley Robinson, describing a voyage in a starship. Space colonisation has been a fictional element over a century since NASA started investigating Mars with scientific speculations. This article aims to highlight the butterfly effect in Kim Stanley Robinson’s Aurora. It also specifies the ecological imbalances due to the lethargic behaviour of the human race. The motive of this theory is to make people understand that even a small droplet can make much difference in an ocean. Beginning with less production of prosperous ends in Cryosleep. Cryosleep technology logically undermines most of the problems in the novel. But, Robinson’s point about the shortcomings of interstellar travel. Through which the butterfly effect of a small cause is added by him.